A new genus and four new species of Gyponini (Insecta: Hemiptera: Cicadellidae) with long ovipositors from Amazonas, Brazil - Da Silva, Marcelo Peixoto Gomes; Gonçalves, Clayton Corrêa; Takiya, Daniela Maeda (Zootaxa, 2022)
A new leafhopper genus of the tribe Gyponini, Domahovana gen. nov., is proposed and described based on four newly described species from Amazonas State, Northern Brazil: Domahovana icamiabas sp. nov. (type species) and Domahovana mani sp. nov. from Reserva Biológica do Cuieiras, Manaus and Domahovana naia sp. nov. and Domahovana yamurikuma sp. nov. from Comunidade Lago Grande no Seringal do Recreio, Rio Gregório, Ipixuna. The new genus can be distinguished from other Gyponini mainly by the combination of the following morphological features: body medium-sized; head short with distinct foliaceous transition between crown and face; forewing with m-cu1 crossvein absent and m-cu2 crossvein basad of r-m1 crossvein for a long distance; male pygofer long and without process; subgenital plate subtriangular, ventrally covered by long hair-like setae; style long and narrow, with a ventromesal tooth; aedeagus atrium with single or paired short ventral processes, shaft short, with dorsal apodeme well developed and expanded laterally; and ovipositor extremely long, narrow and straight, with other terminalia also elongate, a unique feature among female Gyponini. A key to the four known species of Domahovana is provided.